2023
DOI: 10.1039/d2np00073c
|View full text |Cite
|
Sign up to set email alerts
|

Production of high molecular-ordered stilbene oligomers for the study of their biological activity: total synthesis, bio-catalyzed synthesis and production by plant systems

Abstract: Extraordinary progress has been made over the past decade in the chemical synthesis of many stilbene oligomers (>2) as well as in biotechnological methods for the production of these compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Detection of these phytoalexins suggests that their production was rapidly activated after the perception of a pathogen signal, with a high molecular diversity as evidenced by the detection of various oligomeric forms. Moreover, these results demonstrated that DAN is a suitable matrix to study the grapevine leaf surface in the negative mode not only for the detection of simple (stilbene monomers) but also complex stilbene oligomeric phytoalexins by MALDI-MSI. Due to the utilization of a high-resolution and high mass accuracy mass spectrometer (FT-ICR MS), all of the stilbenes mentioned before can be unambiguously distinguished by their masses, except in the case of isomers.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Detection of these phytoalexins suggests that their production was rapidly activated after the perception of a pathogen signal, with a high molecular diversity as evidenced by the detection of various oligomeric forms. Moreover, these results demonstrated that DAN is a suitable matrix to study the grapevine leaf surface in the negative mode not only for the detection of simple (stilbene monomers) but also complex stilbene oligomeric phytoalexins by MALDI-MSI. Due to the utilization of a high-resolution and high mass accuracy mass spectrometer (FT-ICR MS), all of the stilbenes mentioned before can be unambiguously distinguished by their masses, except in the case of isomers.…”
Section: Discussionmentioning
confidence: 83%
“…cinerea, and the first hours of the interaction are crucial for the plant to activate all of the metabolic defense pathways to survive the attack of the pathogen. One of these responses is not only the biosynthesis of resveratrol but also other complex compounds (mainly resveratrol oligomers) that are derived from it. , The accumulation of δ-viniferin at 72 hpi could be considered as a response to the plant accumulating more diverse and more active antifungal compounds than resveratrol itself . In the two different grape cultivars, “Merlot” and “Cabernet Sauvignon”, it was shown that upon a compatible interaction with B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 While RES with trans-configuration, a representative of stilbene compounds, has strong reactivity so that there was a higher level of substitution for hydrogen on the benzene ring. 24,25 In the quantification of reactive hydrogen (Fig. 1(I)-(L)), the hydrogen atoms in the benzene ring and chromone ring of polyphenol decreased in a variety of degrees with the change of hydrogen in the A ring more obvious, which revealed the different activity of reaction sites promoting polyphenol polymerization to form oligomers.…”
Section: Characterization Of the Polymerization Process Of Ppnsmentioning
confidence: 99%
“…These dimers can couple with other resveratrol molecules to form trimers and tetramers. These structurally complex resveratrol-based oligomers have been targeted for synthetic study, and comprehensive de novo synthesis has been explored. ,, …”
mentioning
confidence: 99%